Parathyroidectomia: treatment of secondary hyperparathyroidism. Causes and prophylaxis of disease relapse - BEIŠA, V.; LAGUNAVIČIUS, K.; BEIŠA, A.; STRUPAS, K. (Acta medica Lituanica, 2011)
Background. The growing number of haemodialysis patients and the increasing their life expectancy within the past few years have resulted in a rise of long-term haemodialysis-associated complications. The aim of the paper is to present a case study of a successful surgical treatment of secondary hyperthyroidism and assess the causes of the disease. Materials and methods. A 63-year-old male patient had been on haemodialysis for 18 years; he had undergone parathyroidectomy for secondary hyperparathyroidism 10 years ago. The relapse of the disease was suspected when the patient developed the onset of pruritus and muscle pain. The following tests were performed: biochemical markers of plasma calcium and parathyroid hormone, thyroid ultrasound examination, parathyroid gland 99 mTc MIBI scintigraphy, single photon emission computed tomography of the neck and mediastinum. Results. Elevated calcium (2.73 mmol/l serum) and parathyroid hormone (1352 pg/ml blood plasma) levels were found. Ultrasound examination, 99 mTc MIBI scintigraphy and SPECT revealed parathyroid adenoma of the left inferior thyroid section. The patient underwent surgery in 2011. Remnants of the previously resected parathyroid gland were removed, and an accessory parathyroid gland was found within the thymus; this gland was removed, and partial autotransplantation was performed. The level of the parathyroid hormone decreased to 24 pg/ml during the day after surgery. The histological examination of the removed tissues was performed. Conclusions. Accessory parathyroid glands are usually found within the thymus; therefore, any type of surgical treatment of secondary hyperparathyroidism should include thymectomy. Keywords: parathyroid glands, secondary hyperparathyroidism, haemodialysis, parathyroidectomy